Welcome, caller, this is Chloe - Coriell, Shelley (Laura Ann); 1906-1998. 1958- 1947- (Sandra M.); 1957- (Margaret M.) (New York London Amulet, 2012)
"When big-hearted Chloe Camden's best friend shreds her reputation and her school counselor axes her junior independent study project, Chloe is forced to take on a 'more meaningful' project by joining her school's struggling radio station"-- |c Provided by publisher.
Keywords: Interpersonal relations -- Fiction; Radio broadcasting -- Fiction; High schools -- Fiction; Grandmothers -- Fiction; Young adult fiction